Triple fixed-dose combination in the treatment of hypertension: the results of the Russian observational study TRICOLOR - Yu. A. Karpov; V. M. Gorbunov; N. A. Logunova (Российский кардиологический журнал)
The article presents the main results of the Russian post-marketing multicenter open-label program TRICOLOR (Triple fixed-dose combination in the treatment of hypertension).Aim. To evaluate the antihypertensive efficacy and tolerability of the triple amlodipine/indapamide/perindopril fixed-dose combination, as well as the adherence of hypertensive (HTN) patients to this therapy in actual clinical practice.Material and methods. The program enrolled 1247 outpatients aged 18 to 79 of both sexes with essential HTN. All patients included in the study receive amlodipine/ indapamide/perindopril fixed-dose combination. The patient’s condition was assessed according to four visits: visit 1 — at inclusion, visit 2 — after 2 weeks, visit 3 — after 4 weeks, visit 4 — after 12 weeks of follow-up. At each visit, the achievement of the target blood pressure (BP) <140/90 mm Hg and <130/80 mm Hg. At enrollment and visit 4, quality of life was analyzed using the SF-36 questionnaire and adherence to therapy using a validated 6-question questionnaire.Results. After 12 weeks, a significant decrease in systolic and diastolic BP was recorded — by 33,5 and 14,3 mm Hg, respectively (p<0,001). Target BP <140/90 mm Hg after 12-week follow-up was achieved by the overwhelming majority (93,4%) of patients. After 12 weeks, the proportion of patients with good medical adherence increased from 18,8% to 49,0%, while the proportion of patients with low adherence, on the contrary, decreased from 46,3% to 5,1%.Conclusion. The results of the TRICOLOR program demonstrate a high antihypertensive efficacy, good tolerance and medical adherence of triple amlodipine/indapamide/perindopril fixed-dose combination in patients with essential HTN in actual clinical practice in Russia.